2018
DOI: 10.1002/jsp2.1014
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting tumor necrosis factor‐alpha at time of induced intervertebral disc injury limits long‐term pain and degeneration in a rat model

Abstract: Background: Painful intervertebral disc (IVD) degeneration has tremendous societal costs and few effective therapies. Intradiscal tumor necrosis factor-alpha (TNFα) is commonly associated with low back pain, but the direct relationship remains unclear. Purpose: Treatment strategies for low back pain require improved understanding of the complex relationships between pain, intradiscal pro-inflammatory cytokines, and structural IVD degeneration. A rat in vivo lumbar IVD puncture model was used to 1) determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(89 citation statements)
references
References 92 publications
(195 reference statements)
7
78
1
Order By: Relevance
“…As far as we know, this is the first study evaluating antiinflammatory effects of Etanercept and Tofacitinib within a proinflammatory and degenerative microenvironment of a whole organ IVD culture model. Both, Etanercept and Tofacitinib partially prevented the upregulation of proinflammatory cytokines in IVDs cultured under IDD-like conditions which supports outcome of previous in vitro studies on TNF-α inhibition (Likhitpanichkul et al, 2015;Walter et al, 2015b;Evashwick-Rogler et al, 2018). Moreover, our data confirms the concept of recent work investigating a potential involvement of the IL-6/JAK/STAT3 pathway in IDD (Suzuki et al, 2017).…”
Section: Etanercept and Tofacitinib Reduce Proinflammatory Activity Isupporting
confidence: 90%
See 1 more Smart Citation
“…As far as we know, this is the first study evaluating antiinflammatory effects of Etanercept and Tofacitinib within a proinflammatory and degenerative microenvironment of a whole organ IVD culture model. Both, Etanercept and Tofacitinib partially prevented the upregulation of proinflammatory cytokines in IVDs cultured under IDD-like conditions which supports outcome of previous in vitro studies on TNF-α inhibition (Likhitpanichkul et al, 2015;Walter et al, 2015b;Evashwick-Rogler et al, 2018). Moreover, our data confirms the concept of recent work investigating a potential involvement of the IL-6/JAK/STAT3 pathway in IDD (Suzuki et al, 2017).…”
Section: Etanercept and Tofacitinib Reduce Proinflammatory Activity Isupporting
confidence: 90%
“…Recent studies indicated that the presence of TNF-α causes an upregulation of major catabolic enzymes involving Matrix-Metalloproteinases (MMPs) and A Disintegrin and Metalloprotease with Thrombospondin Motifs (ADAMTS), contributing to advanced structural decay in IDD (Purmessur et al, 2013;Tian et al, 2013;Baptista et al, 2020;Zhou et al, 2020). Moreover, TNF-α is associated with the development of discogenic pain by upregulating pain transmitter substance P (SP) and by attracting nerve ingrowth into the outer annulus fibrosus (Freemont et al, 1997(Freemont et al, , 2002Olmarker and Larsson, 1998;Igarashi et al, 2000;Risbud and Shapiro, 2014;Evashwick-Rogler et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…At this time point, it seems that hydration of the disc by itself (upon vehicle injection) also contributes to reducing hernia volume, although not statistically significantly. This was unexpected, but an effect of vehicle intradiscal injection has been reported before; for example, phosphate-buffered saline (PBS) and TNF-α intradiscal injections induced similar IVD degeneration [22]. Nonetheless, despite Df's short biologic half-life, it can be envisaged for local control of acute inflammation.…”
Section: Discussionmentioning
confidence: 79%
“…16 Solely upregulation of wnt/β-catenin signaling caused no proliferation in rat-derived NP cells however, cell viability was determined to decrease with 50%. 32 Moreover, wnt/β-catenin signaling was demonstrated to regulate tumor necrosis factor (TNF)-α, 47 linking it to IVD degeneration, 50,51 suggesting once more that the balance of canonical and noncanonical signaling is crucial for the outcome of wnt3a treatment. Interestingly, upregulation of the PKC pathway, of the noncanonical signaling pathway, induced cell proliferation in rat NP cells.…”
Section: Nucleus Pulposus Cellsmentioning
confidence: 99%